2005
DOI: 10.1111/j.1365-2753.2005.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Costs and effectiveness of pre‐ and post‐operative home physiotherapy for total knee replacement: randomized controlled trial

Abstract: Although home physiotherapy was as effective and as acceptable to patients as hospital outpatient physiotherapy for unilateral TKR, it was more expensive. Additional pre-operative home physiotherapy did not improve patient-perceived health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
140
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(146 citation statements)
references
References 15 publications
3
140
0
3
Order By: Relevance
“…There are only a few studies on cost-effectiveness of exercise in patients with arthritis (6 -10). However, except for the study by Mitchell et al (8), patients scheduled for joint replacement surgery or patients with total knee or hip replacements were excluded in these studies. Moreover, the definition of exercise differed greatly among the studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few studies on cost-effectiveness of exercise in patients with arthritis (6 -10). However, except for the study by Mitchell et al (8), patients scheduled for joint replacement surgery or patients with total knee or hip replacements were excluded in these studies. Moreover, the definition of exercise differed greatly among the studies.…”
Section: Discussionmentioning
confidence: 99%
“…After screening and detailed evaluation, 48 articles describing 52 interventions met the inclusion criteria and study characteristics are summarised in Table 75. Studies reported interventions in patients before hip (n = 22), knee (n = 21), 500,503,[509][510][511][512][513][514][515][516][517][518][519][520][521][522][523][524][525] or either hip or knee replacement (n = 9). [526][527][528][529][530][531][532][533][534] Interventions focused on optimising pre-surgical health (n = 36), preparation for recovery in hospital (n = 27) and improving long-term outcomes (n = 18).…”
Section: Resultsmentioning
confidence: 99%
“…[526][527][528][529]534 Eighteen interventions were specifically exercise based, 488,494,497,502,503,509,[511][512][513][514][515]519,520,[523][524][525] nine were education based, 52,489,495,500,501,526,527,529 while nine were multifactorial with exercise and education components and, in some cases, an occupational therapy base. 487,493,496,504,507,510,517,521,528 Effect on pre-surgical physical function Physical function before surgery was measured after 21 interventions using WOMAC (physical function or total), SF-36 physical function, HHS, HOOS, HSS, Arthritis Impact Measure Score 2 (AIMS2), AKSS or locally devised scores.…”
Section: Optimising Pre-surgical Healthmentioning
confidence: 99%
“…In a recent Danish trial, an accelerated perioperative care and rehabilitation intervention after TKA turned out to be as effective as but less costly than standard care (12). So far, only a few other studies, representing guidance and physiotherapy, have reported the cost-effectiveness of rehabilitation programs in connection with total knee replacement surgery (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%